Molecular Docking-Based in Silico Evaluation of Leaf Compounds from Coleus blumei Against MRSA - Pongpawan Sethanant; Junhong Kim; Maurizio Martin Cavani Brain (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study aims to investigate the potential of compounds derived from medicinal plants as target protein inhibitors against methicillin-resistant Staphylococcus aureus (MRSA) using an in silico approach. Methodology: This study employed an in silico molecular docking approach to evaluate active compounds from Coleus blumei leaves against MRSA. Target proteins included MecR1, PBP2a, and oxacilloyl-acylated MecR1. Docking was performed using PyRx, PyMOL, and Discovery Studio with molecular data sourced from GC-MS, PubChem, and PDB. Main Findings: The compound Hexahydro-3H-cyclopenta[a]pentalen-3-one, 2,4a,5,6,7,8-hexahydro-4,4,7a-trimethyl-, (4aR,7R,7aS) demonstrated the highest binding affinity across all three MRSA resistance-associated target proteins (PBP2a, MecR1, and oxacillin-acylated MecR1), surpassing penicillin as the control. Molecular interaction visualizations revealed stable hydrogen bonding and hydrophobic interactions with key active site residues, particularly SER, LEU, and PHE in PBP2a. Pharmacokinetic evaluation based on Lipinski's Rule of Five indicated that top-performing compounds, including this compound and Aristolone, exhibit favorable oral drug-like properties. These findings highlight the strong potential of these natural compounds as lead candidates for the development of antibacterial agents targeting MRSA resistance mechanisms. Novelty/Originality of this study: The novelty of this study lies in the utilization of specific natural compounds as potential antimicrobial agents against antibiotic resistance proteins, which have not been widely reported before. This study provides an initial basis for the development of herbal antimicrobial drug candidates for MRSA infections.